Occurrence, Distribution, and Human Exposure of Emerging Liquid Crystal Monomers (LCMs) in Indoor and Outdoor Dust: A Nationwide Study. (June 2022) - Zhang, Shaohan; Yang, Ming; Li, Yuhe; Wang, Yu; Lu, Yuan; Cheng, Zhipeng; Sun, Hongwen
Graphical abstract: Highlights: LCMs were first monitored in indoor and outdoor dust in China on a national scale. The polluted levels of LCMs together with the potential exposure risks should raise concerns for residents' health. Dust ingestion and dermal contact exposure are the major exposure routes for daily intake of LCMs in residents. Abstract: Liquid crystal monomers (LCMs) are a class of emerging, persistent, bioaccumulative, and toxic organic pollutants. They are detected in various environmental matrixes that are associated with electronic waste (e-waste) dismantling. However, their occurrence and distribution in indoor and outdoor dust on a national scale remain unknown. In this study, a dedicated target analysis quantified a broad range of 60 LCMs in dust samples collected across China. The LCMs were frequently detected in indoor (n = 48) and outdoor dust (n = 97; 37 sampled concomitantly with indoors dust) from dwellings, and indoor dust from cybercafés (n = 34) and phone repair stores (n = 22), with median concentrations of 41.6, 94.7, 106, and 171 ng/g, respectively. No significant spatial difference was observed for the concentrations of the total LCMs among distinct geographical regions ( p > 0.05). The median daily intake values of the total LCMs via dust ingestion, dermal contact, and inhalation were estimated at 1.50 × 10 -2, 2.90 × 10 -2, and 8.57 × 10 -6 ng/kg BW/day for adults and 1.47 × 10 -1, 1.22 × 10 -1, and 2.18 × 10 -5 ng/kg BW/day for children, respectively. These estimates suggested higher exposure risks for children and indicated that dust ingestion and dermal contact significantly contribute to the human intake of LCMs. The microenvironmental pollution levels of LCMs together with the potential exposure risks associated with some of these chemicals are of concern for human health.